Hazard Identification in Total Demolition Work - FARAH, FARAH FAZIRA BINTI MOHAMMAD JOHARI; Dr.NOORLI BINTI ISMAIL (Recent Trends in Civil Engineering and Built Environment, 2022)
Demolition industry is one of the most important sector in demolished the building before going to construct a new building and it is growing extremely and progressive and profitable. However, demolition industries are still not well known among Malaysian and initiatives to identify and overcome the hazards in working activities are still lack. The purpose of this study was to identify the hazards in total demolition work involved by implementing the safe work method statement accordance to an appropriate risk control at workplaces. The study methods used are by site visit with the stakeholders. Implementation method will be focusing in achieve the objectives of this study. Therefore, the data collected will be referred to the HIRARC form from the company research conducted as an overview of the total demolition work by phases which starting from the first phase that is an early stages, second phase, middle process of work and third phase which is last stages of working activities. It can conclude, this study conducted is to give a look about how the process and work activities in total demolition involved. The entire of guidelines in total demolition work has been discovered through this research by implemented the safe work method statement according to the right standard of guidelines among the workers and employer. Hence, the findings provide additional knowledge on identifying hazards in total demolition work in Malaysia.